Copy-and-Paste in Medical Student Notes: Extent, Temporal Trends, and Relationship to Scholastic Performance - Monahan, Ken; Ye, Cheng; Gould, Edward; Xu, Meng; Huang, Shi; Spickard, Anderson, III; Rosenbloom, S. Trent; Coco, Joseph; Fabbri, Daniel; Miller, Bonnie (Applied Clinical Informatics, 2019)
Background Medical students may observe and subsequently perpetuate redundancy in clinical documentation, but the degree of redundancy in student notes and whether there is an association with scholastic performance are unknown.Objectives This study sought to quantify redundancy, defined generally as the proportion of similar text between two strings, in medical student notes and evaluate the relationship between note redundancy and objective indicators of student performance.Methods Notes generated by medical students rotating through their medicine clerkship during a single academic year at our institution were analyzed. A student–patient interaction (SPI) was defined as a history and physical and at least two contiguous progress notes authored by the same student during a single patient's hospitalization. For some students, SPI pairs were available from early and late in the clerkship. Redundancy between analogous sections of consecutive notes was calculated on a 0 to 100% scale and was derived from edit distance, the number of changes needed to transform one text string into another. Indicators of student performance included United States Medical Licensing Exam (USMLE) scores.Results Ninety-four single SPIs and 58 SPI pairs were analyzed. Redundancy in the assessment/plan section was high (40%) and increased within individual SPIs (to 60%; p < 0.001) and between SPI pairs over the course of the clerkship (by 30–40%; p < 0.001). Students in the lowest tertile of USMLE step II clinical knowledge scores had higher redundancy in the assessment/plan section than their classmates (67 ± 24% vs. 38 ± 22%; p = 0.002).Conclusion During the medicine clerkship, the assessment/plan section of medical student notes became more redundant over a patient's hospital course and as students gained clinical experience. These trends may be indicative of deficiencies in clinical knowledge or reasoning, as evidenced by performance on some standardized evaluations.
Keywords: Undergraduate Medical Education; clinical clerkship; documentation